2008
DOI: 10.1093/carcin/bgn149
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 3 triggers apoptosis of human prostate cancer cells through a PKC- -dependent mechanism

Abstract: Toll-like receptors (TLRs) are known to play a key role in the innate immune system particularly in inflammatory response against invading pathogens. Recent reports strongly indicate that they play important roles in cancer cells. Prostate cancer represents one of the most common cancer for which no cure is available once metastatic and androgen refractory. Since TLR3 has been recently suggested as a possible therapeutic target in some cancer cell lines, we studied TLR3 expression and functionality in two huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
140
3
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 46 publications
9
140
3
1
Order By: Relevance
“…We further studied the mechanism how PGN induces THP-1 apoptosis. We showed that in THP-1 supernatant adding in with specific mAB of TNF-α, the apoptosis effect of THP-1 was decreased after PGN stimulation, these data demonstrate that PGN induces the apoptosis of human leukemia THP-1 cells in a TNF-α-dependent way, and, there are reports demonstrated that activation of TLRs induced tumor cells apoptosis by other stimulating mechanism (Paone et al, 2008). However, some reports demonstrated that activation of TLRs can trigger proliferation and survival of multiple cancer cells.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We further studied the mechanism how PGN induces THP-1 apoptosis. We showed that in THP-1 supernatant adding in with specific mAB of TNF-α, the apoptosis effect of THP-1 was decreased after PGN stimulation, these data demonstrate that PGN induces the apoptosis of human leukemia THP-1 cells in a TNF-α-dependent way, and, there are reports demonstrated that activation of TLRs induced tumor cells apoptosis by other stimulating mechanism (Paone et al, 2008). However, some reports demonstrated that activation of TLRs can trigger proliferation and survival of multiple cancer cells.…”
Section: Discussionsupporting
confidence: 54%
“…The reports have previously demonstrated that ligand recognition by TLRs triggers human prostate cancer cells and glioma cells apoptosis through TLR3 and TLR9 respectively (Paone et al, 2008). Recently, we also demonstrated that PGN, the ligand of TLR2 induced THP-1 apoptosis by time-and dose-dependent manner.…”
Section: Discussionmentioning
confidence: 60%
“…cM362-140 activated TICAM-1 for DC maturation, but barely induced chemokine production or necroptosis in tumour cells ( Supplementary Fig. 10), which were reported as a direct action of poly(I:C) 29,30 . Therefore, cM362-140 eliminates major inflammatory responses caused by poly(I:C).…”
Section: Discussionmentioning
confidence: 92%
“…This reaction may be due to the established balance favoring apoptosis rather than the proliferation of cancer cells under TLR ligation [68]. This balance may depend on the concentration of certain cytokines and the time of stimulation [69].…”
Section: The Results Of Tlr Activation -Tlrs In Carcinogenesismentioning
confidence: 99%